Case Report: Micafungin for treating Candida glabrata urinary infection: a clinical case in a premature neonate - Parramon-Teixido, Carlos Javier; Garcia Esquerda, Carme; Frick, Marie Antoinette; Tripodi, Cinzia; Gomez-Ganda, Laura; Ruiz-Campillo, Cesar Wenceslao; Cabañas-Poy, Maria Josep (Frontiers in Pediatrics, 2024)
Urinary tract infections (UTIs) associated with indwelling urinary catheterization (IUC) in premature newborns (PNBs) pose a significant challenge in neonatal intensive care units (NICUs) due to the vulnerability of this population to infections and the necessity of invasive procedures. While bacterial UTIs have historically been predominant, there is a rising incidence of fungal pathogens, particularly non-albicans Candida strains like Candida glabrata and Candida tropicalis, attributed to broad-spectrum antibiotic use. Diagnosis of fungal UTIs in a PNB relies on culturing Candida spp. from properly collected urine samples, particularly critical in very low birth weight (VLBW) PNBs because of the risk of invasive candidiasis and associated complications. We present a case of an extremely premature newborn (EPNB) successfully treated for a UTI caused by C. glabrata with micafungin. Our case exhibits micafungin as a potentially safe and effective alternative for treating C. glabrata UTIs in neonates.